1993
DOI: 10.1159/000163790
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Immune Reactivity and Neuroendocrine Alterations Related to Chronic Stress in Spinal Cord Injury and Stroke Patients

Abstract: Both natural and adaptive immune responses were found to be strikingly decreased 2 weeks after injury in 54 spinal cord injury and stroke patients, i.e., 28 quadriplegics, 21 paraplegics and 5 stroke patients, compared with those of age-matched controls. All values are expressed as means. Natural-killer (NK)-cell function decreased to 21.0% 2 weeks after spinal cord injury compared with 48.6% in controls. At 2 weeks, plasma ACTH values increased to 17.0 pg/ ml in patients compared with 11.2 pg/ml in controls, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…It is thought that CNS injuries break the delicate interplay between the immune system and CNS, resulting in secondary immunosuppression (60). Many studies have shown a reduced NKCA of blood NK cells of patients with spinal cord injury and TBI (61)(62)(63). Although the CD56 bright population stayed unchanged, the CD56 dim subtype was decreased, and this correlated with the occurrence of infections after TBI (64).…”
Section: Nk Cell Modifications Associated With Cns Disordersmentioning
confidence: 99%
“…It is thought that CNS injuries break the delicate interplay between the immune system and CNS, resulting in secondary immunosuppression (60). Many studies have shown a reduced NKCA of blood NK cells of patients with spinal cord injury and TBI (61)(62)(63). Although the CD56 bright population stayed unchanged, the CD56 dim subtype was decreased, and this correlated with the occurrence of infections after TBI (64).…”
Section: Nk Cell Modifications Associated With Cns Disordersmentioning
confidence: 99%
“…4,[14][15][16][17][18] Other theories as to why SCI patients may be more prone to developing bladder cancer include an increased urine contact time, due to less frequent voiding, altered growth factor expression, and hormonal and immune system changes (see Table 3 for a summary of risk factors). 34 It is also possible that denervation of the bladder leads to the development of urothelial dysplasia.…”
Section: Risk Factors For Development Of Bladder Cancer In Sci Patientsmentioning
confidence: 99%
“…Clinical data show that human spinal cord injury (SCI) is accompanied by profound immunological impairment (Cruse et al, 1993;Nash, 2000). Undoubtedly, immune dysfunction after SCI contributes to the significant increase in mortality caused by septicemia, diseases of the lung (e.g., pneumonia), gastrointestinal tract or urinary system (DeVivo et al, 1989).…”
Section: Introductionmentioning
confidence: 99%